KARAKTER GENERASI MILENIAL DALAM BERWISATA DI DESTINASI WISATA BUDAYA LAWANG SEWU DAN KOTA LAMA SEMARANG - Vina Dini Pravita (Pringgitan, 2020)
This paper aims to find out how the character of the millennial generation in traveling in the destination of Lawang Sewu and the Old Town Region of Semarang. The study used a descriptive qualitative method followed by interviews with visitors to the two tourism destinations which resulted in the conclusion that the character of the millennial generation was greatly influenced by cell phone use both in obtaining information on the selection of destinations to be visited and the activities carried out during the tour. It can be concluded from the writing that millennial generation cannot be separated from cellular phones in everyday life. This has a big influence on the implementation of decision making, in this case the selection of destinations and attitudes when traveling.Keywords: millenial generation, destination, cell phone, character